Post-acquisition performance of emerging market multinationals in developed markets, impact of institutional distance and international experience. Evidence from South Africa. - Onaji-Benson, Theresa (University of Pretoria, 2023)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2022.